2013
DOI: 10.1089/cap.2012.0048
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Administration of Intranasal Oxytocin Is a Safe and Promising Therapy for Early Adolescent Boys with Autism Spectrum Disorders

Abstract: Although our results on the efficacy of long-term nasal OT therapy still remain controversial, to the best of our knowledge, this is the first report documenting the safety of long-term nasal OT therapy for children with ASD. Even though our data are too preliminary to draw any definite conclusions about efficacy, they do suggest this therapy to be safe, promising, and worthy of a large-scale, double-blind placebo-controlled study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(109 citation statements)
references
References 13 publications
2
102
2
3
Order By: Relevance
“…In this context, oxytocin has significant appeal as an innovative adjunctive therapy for autism spectrum disorder (11)(12)(13) and has shown promise as an early intervention (e.g., refs. [15][16][17]. Although much remains unknown about the influence of exogenous oxytocin on infants, the present study presents promising results, suggesting potential social benefits.…”
Section: Close Proximitymentioning
confidence: 55%
“…In this context, oxytocin has significant appeal as an innovative adjunctive therapy for autism spectrum disorder (11)(12)(13) and has shown promise as an early intervention (e.g., refs. [15][16][17]. Although much remains unknown about the influence of exogenous oxytocin on infants, the present study presents promising results, suggesting potential social benefits.…”
Section: Close Proximitymentioning
confidence: 55%
“…ASD has been linked to TPJ functioning (e.g. Lombardo et al, 2011), and recent research suggests that OT has positive effects on social processing in ASD (Green and Hollander, 2010;Yamasue et al, 2012;Miller, 2013;Tachibana et al, 2013). Furthermore, it has been demonstrated that individuals with ASD show larger interference effects in the imitation-inhibition task and deficits in the imitation-inhibition task have been linked to TPJ functioning in ASD (Spengler et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…Open label case studies and uncontrolled cohort studies suggest potential benefits of nasal oxytocin to treat observed autism symptoms using repeated dosing (81,82). Two published randomized placebo-controlled trials providing nasal oxytocin over an extended period to 9 evaluate this.…”
Section: The Effect Of Oxytocin As An Extended Treatment For Autism Smentioning
confidence: 99%